Growth hormone receptor contributes to the activation of STAT5 in the hypothalamus of pregnant mice. (23rd January 2022) - Wasinski, Frederick; Teixeira, Pryscila D.S.; List, Edward O.; Kopchick, John J.; Donato, Jose
Graphical abstract: Highlights: Increased pulsatile growth hormone (GH) secretion in late pregnant mice. Neuronal GH receptor deletion (Nestin ΔGHR mice) blunts GH-induced pSTAT5 in the brain. Normal pSTAT5 expression in the paraventricular nucleus of pregnant Nestin ΔGHR mice. Reduced pSTAT5 expression in the arcuate nucleus of pregnant Nestin ΔGHR mice. Reduced pSTAT5 expression in the ventromedial nucleus of pregnant Nestin ΔGHR mice. Abstract: Growth hormone (GH) receptor (GHR) signaling induces the phosphorylation of the signal transducer and activator of transcription 5 (pSTAT5) in the cells of several tissues including in the hypothalamus. During pregnancy, several STAT5-recruiting hormones (e.g., prolactin, GH and placental lactogens) are highly secreted. However, the precise contribution of GHR signaling to the surge of pSTAT5 immunoreactive neurons that occurs in the hypothalamus of pregnant mice is currently unknown. Thus, the objective of the present study was to determine whether GHR expression in neurons is required for inducing pSTAT5 expression in several hypothalamic nuclei during pregnancy. Initially, we demonstrated that late pregnant C57BL/6 mice (gestational day 14 to 18) exhibited increased pulsatile GH secretion compared to virgin females. Next, we confirmed that neuron-specific GHR ablation robustly reduces hypothalamic Ghr mRNA levels and prevents GH-induced pSTAT5 in the arcuate, paraventricular and ventromedial hypothalamic nuclei. Subsequently, the number of pSTAT5 immunoreactive cells was determined in the hypothalamus of late pregnant mice. Although neuron-specific GHR ablation did not affect the number of pSTAT5 immunoreactive cells in the paraventricular nucleus of the hypothalamus, reduced pSTAT5 expression was observed in the arcuate and ventromedial nuclei of pregnant neuron-specific GHR knockouts, compared to control pregnant mice. In summary, a subset of hypothalamic neurons requires GHR signaling to express pSTAT5 during pregnancy. These findings contribute to the understanding of the endocrine factors that affect the activation of transcription factors in the brain during pregnancy.